GE_GERICHTE P/17550/2008 vom 9. Januar 2015 - GE Cour de justice (2015)
LÉSION CORPORELLE SIMPLE; LÉGITIME DÉFENSE; ATTÉNUATION DE LA PEINE; EXEMPTION DE PEINE | CP.123.1; CP.126; CP.15; CP.47; CP.48.c; CP.52; CPP.135.2; CPP.422